(3dhGeY GdfcGJs - (3GdejKej, eMehO Hf LYaQ Hf HGbQ, J (B1308 (3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO(B... (3gPG gh GdLRA GdNGeS ef CLRGA cJGH(B... (3cJHJg JPcQI dfaSj hddWGdHjf (B... (3hgh eTJed Ydi cJGH GdQgf(B...s
(3BNQgG (B:s
(3Edi ReGf GdHjY MJi jJQJH Ydjg hbhY GdHjY Yf EPf hEf cGf ebOeG Ydi GSJUMGH HbGA GdQgGfI (B... (3hGddg GdgGOjs
(3JHUQI GdYfhGf (B:s
(3TQM GdTQGFYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 470s
(3GdPQjYI HQbe(B: 470s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis